Pengembangan dan Pelatihan Pemerahan Susu Kambing Etawa di Desa Jenisgelaran Kecamatan Bareng - Kevin Khanza Pangestu; Zein, Selina Ashilah; Rusdi Alim Wibawa Jati; Maharani Nur Rokhmah Akhsanti; Mu’tasim Billah (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
Jenisgelaran Village has many MSMEs that have the potential to be developed to become typical products of the village. One of them is Goat Tawa which is Etawa goat's milk business. These products are in great demand by the public and quite well known so that buyers also come from outside Bareng District. The efforts to develop and advance this MSME such as updating the design on the bottle packaging as well as the product logo and the correct procedure for milking Etawa goats so that the resulting product has the same quality and taste and is sterile. From the training carried out, it resulted in new bottle packaging designs and logos and the Etawa goat milk MSME actors applied the correct milking procedure.